Attention region detection and tracking for observing a person manipulating day–to–day objects. (15th March 2013) - Nagahama, Kotaro; Nishino, Tomohiro; Yamazaki, Kimitoshi; Okada, Kei; Inaba, Masayuki
This paper presents a method for robots tracking multiple important regions with proper resolution while the robot is observing a person in daily environments. The system consists of a visual function to track end points and a composite vision system. The visual function uses 'continuous disparity filtering' that is an expansion of zero disparity iltering and other evaluation functions to track a person's head, hands and tips of tools. Besides, we developed a composite vision head with wide–angle cameras and zoom–enabled stereo cameras. We tested the visual function and the vision system by experiments to track a human head and hands, and to change the attention position to be captured with high resolution. These results showed the effectiveness of our approach.